Role of ubiquitin-specific proteases in programmed cell death of breast cancer cells - Wen Yan; Shasha Xiang; Jianbo Feng; Xuyu Zu (Genes and Diseases)
Breast cancer (BC) is the most common malignant tumor and the leading cause of cancer-related deaths among women worldwide. Great progress has been recently achieved in controlling breast cancer; however, mortality from breast cancer remains a substantial challenge, and new treatment mechanisms are being actively sought. Programmed cell death (PCD) is associated with the progression and treatment of many types of human cancers. PCD can be divided into multiple pathways including autophagy, apoptosis, mitotic catastrophe, necroptosis, ferroptosis, pyroptosis, and anoikis. Ubiquitination is a post-translational modification process in which ubiquitin, a 76-amino acid protein, is coupled to the lysine residues of other proteins. Ubiquitination is involved in many physiological events and promotes cancer development and progression. This review elaborates the role of ubiquitin-specific protease (USP) in programmed cell death, which is common in breast cancer cells, and lays the foundation for tumor diagnosis and targeted therapy.